Challenges of data sharing in European Covid-19 projects: A learning opportunity for advancing pandemic preparedness and response - Evelina Tacconelli; Anna Gorska; Elena Carrara; Ruth Joanna Davis; Marc Bonten; Alex W. Friedrich; Corinna Glasner; Herman Goossens; Jan Hasenauer; Josep Maria Haro Abad; José L. Peñalvo; Albert Sanchez-Niubo; et al. (Elsevier, 2022)
Summary: The COVID-19 pandemic saw a massive investment into collaborative research projects with a focus on producing data to support public health decisions. We relay our direct experience of four projects funded under the Horizon2020 programme, namely ReCoDID, ORCHESTRA, unCoVer and SYNCHROS. The projects provide insight into the complexities of sharing patient level data from observational cohorts. We focus on compliance with the General Data Protection Regulation (GDPR) and ethics approvals when sharing data across national borders. We discuss procedures for data mapping; submission of new international codes to standards organisation; federated approach; and centralised data curation. Finally, we put forward recommendations for the development of guidelines for the application of GDPR in case of major public health threats; mandatory standards for data collection in funding frameworks; training and capacity building for data owners; cataloguing of international use of metadata standards; and dedicated funding for identified critical areas.